Analysis of Students Problem-Solving Ability in Solving Improper Integral Problems - Hanifah, Hanifah; Rum, Ahbi Mahdianing (ARITHMETIC: Academic Journal of Math, 2023)
This study aimed to determine the student’s problem-solving-ability using Polya stages in solving Improper Integral questions in online Integral Calculus Learning through zoom applying Student-Centered Learning. It is very rare to find the research that examines students' problem-solving abilities in solving improper integral problems. The research method used in this study was ex-post facto research. The research subjects were 14 students from class B in the third semester of the Mathematics Study Program FKIP UNIB 2020/2021 getting grades A and A- in Integral Calculus Learning. The analysis in Polya stages consisted of Understanding the Problem (P1); Devising a Plan (P2); Carrying out the Plan (P3); and Looking Back (P4. The instruments used to collect data were improper integral test sheets, analysis guide sheets, and open questionnaires. The result showed the mean score of the student’s problem-solving ability was 74.02. The mean value in each stage: P1 = 79.91; P2 = 79.46; P3 = 72.77; and P4 = 65.18. It was concluded that students already had good abilities in understanding problems and planning solutions.